Tìm x+y biết (x-2)^2 + x^2 + (y-x)^2 = 2. (x,y là số thực nhé)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 3xy2 - 45x2y = 3xy( y - 15x )
b) 25y2 - 4x2 + 4x - 1
= 25y2 - ( 4x2 - 4x + 1 )
= ( 5y )2 - ( 2x - 1 )2
= ( 5y - 2x + 1 )( 5y + 2x - 1 )
c) x2 - 8x - 33
= x2 - 11x + 3x - 33
= x( x - 11 ) + 3( x - 11 )
= ( x - 11 )( x + 3 )
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 4.
a) 3xy2 - 45x2y = 3xy( y - 15x )
b) 25y2 - 4x2 + 4x - 1
= 25y2 - ( 4x2 - 4x + 1 )
= ( 5y )2 - ( 2x - 1 )2
= ( 5y - 2x + 1 )( 5y + 2x - 1 )
c) x2 - 5x + xy - 5y
= x( x - 5 ) + y( x - 5 )
= ( x - 5 )( x + y )
d) x2 - 8x - 33
= x2 + 3x - 11x - 33
= x( x + 3 ) - 11( x + 3 )
= ( x + 3 )( x - 11 )
Bài 5.
a) A = ( x - 2 )3 - x2( x - 4 ) + 8
= x3 - 6x2 + 12x - 8 - x3 + 4x2 + 8
= -2x2 + 12x
B = ( x2 - 6x + 9 ) : ( x - 3 ) - x( x + 7 ) - 9
= ( x - 3 )2 : ( x - 3 ) - x2 - 7x - 9
= x - 3 - x2 - 7x - 9
= -x2 - 6x - 12
b) Với x = -1 thì A = -2.(-1)2 + 12.(-1) = -2 - 12 = -14
![](https://rs.olm.vn/images/avt/0.png?1311)
= x2 + x - 3x - 3
= x(x + 1) - 3(x + 1)
= (x + 1)(x - 3)